Kinematic model for simulating mucosal wave phenomena on vocal folds. (March 2019) - Kumar, S. Pravin; Švec, Jan G.
Highlights: Kinematic model simulates vocal fold vibrations and mucosal waves. It allows parametrically changing the vocal fold shape, glottal configuration and vibrational properties. It generates synthetic kymograms with comparable appearance to that of clinical kymograms. Coronal view of vocal fold dynamics is simulated, which is normally invisible in laryngoscopic views. It provides a tool to study vocal fold vibrations, mucosal waves, their underlying mechanics, and kymograms. Abstract: Mucosal waves have been found to be important for evaluating vocal fold vibrations in laryngological practice. While they are routinely evaluated visually, the knowledge on the physical phenomena related to mucosal wave propagation is limited. Kymographic imaging, in particular, reveals various mucosal wave features that deserve more understanding in order to advance functional diagnostics of voice disorders. Here, a kinematic model is presented which simulates mucosal waves on human vocal folds. The vocal fold geometry is based on a parametrically adjustable M5 model. A kinematic rule is used for simulating the propagation of the mucosal wave from the bottom of the vocal folds upwards and laterally over the upper vocal fold surface. The model maps the changes of the coronal shape of the vocal folds through vibration cycles. The vibration characteristics including the mucosal wave movements are then visualized using a synthetic kymogram graphically obtained through a local illumination method. The model can serve as an educational and research tool for studying the mucosal wave features and their appearance in laryngeal kymographic images.